Numerical simulations of irreversibility for nonlinearly radiative and chemically reactive flow of Maxwell fluid - Debozani Borgohain (Discover Applied Sciences)
Abstract The cooling & heating phenomena are involved in numerous engineering-industrial operations and have become essential for the development of thermal electronic & energy devices. In this paper, study is performed on entropy production with an emphasis on nonlinearized thermal radiation and viscous dissipation under the consequence of time dependent magnetic field for an unsteady flow of chemically reactive Maxwell fluid in Darcian porous media. The flow governing equations are solved numerically in MATLAB (bvp4c). Graphs are plotted demonstrating the distribution of irreversibility and entropy generation. Numerical results of the impressions of material parameters on Skin friction, Nusselt and Sherwood numbers are also tabulated. This study establishes that the efficiency of thermal devices can be upgraded by higher order chemical reaction and viscous dissipation effects together with the compressed nonlinear radiation and magnetic effects. Also, unsteadiness in the flow, porosity and magnetic effects enhance the shearing stress on the surface leading to greater surface friction while solar radiation and surface heating due to nonlinearity in radiative force favour the heat transferable rate leading to an improvement in convection rate. These inferences can be helpful in the development of proper thermal electronic and industrial devices with solar radiation applications.